Climate shocks and economic resilience: Evidence from Zambia's formal sector - Kwabena Adu-Ababio; Evaristo Mwale; Rodrigo Carvalho Oliveira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Low-income countries face the combined challenges of climate shocks and limited domestic revenue mobilization, yet these issues are rarely studied together. This paper provides new evidence on the impact of climate shocks on firm performance and tax revenue in a lowincome country context, using firm-level data from Zambia. We find that extreme weather events, such as excessive rainfall and high temperatures, significantly reduce firms' sales, input purchases, and tax collection, particularly in sectors such as manufacturing, retail, accommodation, and construction. Firms respond by reducing employment and wages, reflecting a decline in productivity. Our findings highlight the need to consider the combined effects of climate shocks on both formal sector productivity and government revenue in developing countries, where taxation on services and goods (e.g. VAT) represents a larger share of government budgets.
Keywords: H32; Q54; Q56; 330; value-added tax (VAT); climate shocks; Zambia; domestic revenue mobilization; firms